Analyzing Success Factors in Developing Mobile Applications for Farmers in Thailand Using Analytic Hierarchy Process Technique - Kunlerd, Attapol; Nabumroong, Boonlueo; Jantarakomet, Kraisak; Ruttanaprasert, Ruttanachira; Burana, Kunlachat (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2024)
This study applies the Analytic Hierarchy Process (AHP) as a robust decision-making framework to address critical gaps in risk management and criteria prioritization within mobile application development for the agricultural sector, specifically focusing on Thai rice farmers. The research identifies essential factors influencing technology adoption through input collected from 100 rice farmers in Surin Province. Using AHP, these factors were systematically ranked, with "ease of use," "provision of up-to-date information," and "support" emerging as the most significant criteria. Based on these insights, three mobile application prototypes were developed, with Mobile App 1 achieving the highest AHP score of 0.633, demonstrating superior alignment with user requirements. Subsequent evaluations of user satisfaction reinforced these findings, with "ease of use" scoring the highest (4.60), followed by "perceived usefulness" (4.10). The findings underscore AHP’s efficacy in mitigating risks and aligning application features with user demands, thereby enhancing adoption effectiveness. This study contributes novel insights into leveraging AHP as a precision tool for guiding mobile application development in agriculture and provides a replicable framework for addressing user-centric challenges. Future research should investigate integrating AHP with emerging technologies to drive innovation and sustainable solutions in agricultural practices.